Health Literacy as a Determinant of Treatment Adherence and Infectious Disease Prevention Behavior: A Conceptual Analysis - Felicidade do Rosario (Green Publisher, 2026)
Health literacy is a crucial determinant of public health behavior, particularly in the control of infectious diseases in developing countries like Timor-Leste. Individuals' limited ability to access, understand, and use health information often results in low medication adherence and weak preventive behavior. This article aims to conceptually analyze the role of health literacy as a determinant of medication adherence and infectious disease prevention behavior from the perspective of social determinants of health. This study uses a literature review method with a narrative synthesis approach to relevant theories and empirical findings. The analysis shows that health literacy contributes by improving understanding of medical instructions, strengthening self-efficacy, and the ability to make informed decisions. Adequate literacy encourages adherence to therapy and consistent preventive behaviors, such as hygiene practices and utilization of health services. Conceptually, health literacy is positioned not only as an individual capacity but also as a structural factor influenced by the education system and public policy. Therefore, strengthening health literacy is a key strategy in infectious disease control.